2019
DOI: 10.4054/demres.2019.40.49
|View full text |Cite
|
Sign up to set email alerts
|

Changes in seasonality of births in Poland in the years 1900–2009

Abstract: BACKGROUNDTo date, several countries have documented changes over time in the pattern of seasonal fluctuations of births. Differences in these changes between countries allow us to better understand the social and economic factors determining birth seasonality. OBJECTIVEThe aim of the present study is to explore birth seasonality in Poland over a period of 110 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…Other studies have shown changes in the magnitude [ 69 , 79 ] or the shape of the birth pattern over time [ 11 ]. Our study also shows such a change: a decrease/increase in precipitation/temperature within the last 30 years parallel to a shift in the timing of the second peak of births in the year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have shown changes in the magnitude [ 69 , 79 ] or the shape of the birth pattern over time [ 11 ]. Our study also shows such a change: a decrease/increase in precipitation/temperature within the last 30 years parallel to a shift in the timing of the second peak of births in the year.…”
Section: Discussionmentioning
confidence: 99%
“…This is a classic issue in demography [e.g. 10 , 11 ], whose significance has been demonstrated in the vast majority of populations from the broad national scale [e.g. 12 ] to the local scale [ 13 ], but with considerable differences in pattern, magnitude and timing [e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notable differences in patterns have been observed for marital and nonmarital fertility (e.g., Régnier-Loilier and Divinagracia 2010), for births of different parities (e.g., Haandrikman 2004), for populations of different faiths (e.g., Friger, Shoham-Vardi, and Abu-Saad 2009), by mother's education level (e.g., Bobak and Gjonca 2001), and by mother's age (e.g., Dahlberg and Andersson 2018). Several studies have also demonstrated marked changes in the seasonality patterns over time (e.g., Cypryjański 2019;Compton and Tedds 2016), sometimes accompanied by a long-run reduction in the amplitude of seasonality (e.g., Régnier-Loilier and Divinagracia 2010;Cancho-Candela, Andrés-de Llano, and Ardura-Fernández 2007).…”
Section: Introductionmentioning
confidence: 99%